Fostering EFL Learners’ Writing Skills through Blog-Assisted Language Learning (BALL) - Sari, Silvia Nurmila; Wulyani, Anik Nunuk; Suharyadi (VELES Voices of English Language Education Society, 2024)
Blog-Assisted Language Learning (BALL) provides a platform for students to enhance their language skills through interactive and engaging activities. These activities include peer review and feedback, interactive discussions, reflective journals, and multimedia integration. This study aims to investigate the specific impact of BALL on improving EFL learners' writing performance, addressing the problem of how this innovative approach can enhance various aspects of writing skills. This study was conducted using classroom action research in one cycle, involving 18 vocational school students. Data were gathered through writing tests, observation checklists, and questionnaires. The findings revealed that implementing Blog-Assisted Language Learning significantly enhanced the learners’ writing performance and attitudes toward learning English. The students showed improvement in content, organization, vocabulary, language use, and mechanics of their writing. The average score increased from 71.61 in the pretest to 81.9 in the posttest. All students were engaged in the teaching and learning process, and they found using a blog to promote language acquisition to be an enjoyable activity. Additionally, a Paired Sample t-Test showed a significant difference between the students' overall scores pre-test and post-test, with a level of significance of 0.000, indicating that the implementation of Blog-Assisted Language Learning had a statistically significant impact on improving the students' writing performance. Therefore, Blog-Assisted Language Learning proves to be a valuable strategy for enhancing EFL learners' writing skills, and its interactive and enjoyable nature can motivate students, creating a more dynamic and student-centered learning environment.